The feasibility and acceptability of male circumcision among men, women, and health providers of the Altagracia Province, Dominican Republic - Brito, Maximo O. (2010)
BACKGROUND: Male circumcision (MC) is an effective strategy to reduce the risk of HIV acquisition in men. The objective of the present study was to evaluate the feasibility of introducing MC in the Altagracia Province and to qualitatively assess the knowledge and acceptability of MC among men, women, and health providers. METHODS: Two surveys were administered to providers. The first, assessed their experience and knowledge of MC and the second, a “Health Facility Profile,” included an inventory of available surgical materials in the clinics. Fourteen focus group discussions were conducted to evaluate the acceptability of MC. RESULTS: Forty-three providers were interviewed at 37 clinics. Median age was 33 years (range 23–55 years). Most were physicians (91%) employed by the government. Only 23% had experience with MC. Almost universally (95%), providers knew that MC has health benefits. All agreed that MC improves hygiene and 67% knew that MC decreases the risk of HIV infection. Only six clinics provided HIV counseling and testing and most lacked adequate surgical facilities and equipment. Findings of the qualitative study showed that about half the men and the majority of women were accepting of MC. CONCLUSIONS: Men, women, and providers in the Dominican Republic may be accepting of MC. Education about the benefits of the procedure is needed in the community.